Efficacy of Dietary Chenopodium album Extract on Some Health Parameters, Digestive Enzymes and Growth Performance in Juvenile Cyprinus carpio - Amhamed, İman Daw; Mohamed, Gamaia Ali; Almabrok, Ahmed Alhadi; Altief, Tarek Abdalsalam Salem; Bi̇len, Soner (Alinteri Zirai Bilimler Dergisi, 2018)
The present study was conducted to investigate the efficacy of a Chenopodium album aqueous methanolic extract supplementation on the immunological and haematological indices, digestive enzyme activity and growth performance of the common carp (Cyprinus carpio). C. album was added to a basal diet at the rate of 0 (CA0), 0.1 (CA0.1), 0.5 (CA0.5) and 1 g kg−1 (CA1), and C. carpio was fed this diet for 45 days. Respiratory burst activity was significantly increased in all experimental groups on days 15 and 30 compared to the control (P < 0.05). Lysozyme activity was significantly increased over all sampling times compared to the control except in CA1 (P < 0.05). Myeloperoxidase activities were significantly increased in all experimental groups compared to the control (P < 0.05). Haematological parameters were significantly decreased compared to the control (P < 0.05). Trypsin and lipase activities were significantly increased in CA0.5 and CA1 compared to the control (P < 0.05). Amylase activity was significantly improved in all experimental groups compared to the control (P < 0.05). Final weight, weight gain and SGR were significantly enhanced in CA0.1 and CA1 compared to the control (P < 0.05). FCR was not different in any of the experimental group (P > 0.05). These results demonstrate that dietary supplementation with an aqueous methanolic extract has beneficial effects on the immune responses, digestive enzyme activity and growth performance of C. carpio.
Keywords: Chenopodium album; common carp (Cyprinus carpio); haematology; immunological indices; digestive enzyme activity; 3. Good health